Chemistry of bio-based polymers - Fink, Johannes Karl. (Hoboken, New Jersey : Wiley, 2014)
"Because of the recent explosion of interdisciplinary research in renewable polymers, the knowledge base is scattered and it is now timely to have an overview from a respected chemist and successful author. The book focuses on biopolymers as well as low molecular compounds that can be synthesized from renewable polymers. After introducing general aspects of the field, the subsequent chapters then look at the chemistry of biodegradable polymeric types sorted by their chemical compounds, including the synthesis of low molecular compounds. The factors influencing degradation and biodegradation of polymers for food packaging in various environments is detailed at length. The medical applications covered concentrate on controlled drug delivery, temporary prostheses, and scaffolds for tissue engineering. The author then turns his attention to renewable resources for fabricating biofuels and argues for localized biorefineries as biomass feedstocks are more efficiently handled locally"--
Includes bibliographical references and index.
Text in English.
Description based on print version record and CIP data provided by publisher.
Keywords: Biodegradable plastics; TECHNOLOGY & ENGINEERING / Chemical & Biochemical; Biodegradable plastics; Electronic books; Electronic books